Preoperative Simulation in Planning Rhinoplasty: Evaluation from Patients' and Surgeons' Perspectives - Aksakal, İbrahim Alper; Keles, Musa Kemal; Engin, Murat Sinan; Aydoğdu, İlhami Oğuzhan; Küçüker, İsmail (Facial Plastic Surgery, 2017)
Among aesthetic surgery procedures, rhinoplasty is one of the most common. Preoperative simulations have become increasingly commonplace through the recent years along with a controversy regarding their use. Although capable of building a solid rapport between the surgeon and the patient by visualizing the end result, it can also prove to be a liability for a surgeon who is not confident about delivering the result which has been put on screen. The objective of this study is to evaluate the outlook of the surgeons and patients on preoperative simulations. Plastic surgeons who perform rhinoplasty and individuals who consider rhinoplasty were surveyed via an online questionnaire system. Their opinions about the practice of simulation were questioned and they were asked to distinguish between simulated and actual postoperative results. Statistical analyses were performed using SPSS software. Major factors influencing the decision-making process of patients were the availability of preoperative simulation, being shown appealing results of the surgeon's previous work and a personal reference from a patient with an appealing result. Within the health care professionals, it has been observed that experienced surgeons are more confident about using simulations, while inexperienced ones are daunted by being bound with a visual contract (p < 0.05). However, it has been noted that the preference of withholding the simulation or providing a copy to the patient was similar in all experience levels (p > 0.05). In conclusion, our findings suggest that the patients' self-consciousness regarding preoperative simulations seem to grow faster than the surgeons' confidence in their use. Level of evidence is Level V.
Keywords: simulation; rhinoplasty; preoperative